The influence of substitutions on elite soccer teams' performance - Gomez, M.-A.; Lago-Penas, C.; Owen, A. L. (International Journal of Performance Analysis in Sport, 2016)
The aim of the present study was to identify the effects of substitutions on soccer team's performance with regard to match conditions, positional roles and the differences amongst team outputs of three variables: ball possession, shots and ball regains. The sample composed of 292 substitutions obtained from 50 elite soccer games. Variables studied were: minute of substitution, substitution number, yellow card, player in and player out playing positions, ball possession percentage, shots on target, balls regained, and situational variables (match-status, quality of opposition, match location and match outcome). The results showed that: (i) most of the first and second substitutions occurred during the 61 to 90 minute period, while the third substitution occurred predominantly during the 76 to 90 minutes period. When the teams were losing they made the substitutions before than when drawing or winning and home teams made the substitutions before than the away teams. The majority of the substitutions involved midfield (57.1%) and forwards (27.1%) players; (ii) substitution strategies depend on contextual-related variables: the better the quality of opposing team the later the substitutions will take place; and (iii) the coaches' substitution time strategies can alter the playing tactics and final outcome in the match. The present study provides to the coaches new information on substitutions patterns that can be easily integrated into their overall coaching strategy.